2020
DOI: 10.1371/journal.pone.0242476
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of COVID-19 pandemic on public transit demand in the United States

Abstract: The COVID-19 pandemic and related restrictions led to major transit demand decline for many public transit systems in the United States. This paper is a systematic analysis of the dynamics and dimensions of this unprecedented decline. Using transit demand data derived from a widely used transit navigation app, we fit logistic functions to model the decline in daily demand and derive key parameters: base value, the apparent minimal level of demand and cliff and base points, representing the initial date when tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(186 citation statements)
references
References 18 publications
(19 reference statements)
4
174
0
Order By: Relevance
“…Regression analysis revealed minimum demand for public transport was observed during COVID-19 in communities with higher proportions of critical employees and vulnerable groups (African American, Hispanic, Female, and people over 45 years of age). Around half of the agencies suffered a decline before the local spread of COVID-19 possibly began; most of these are in the Midwest of the United States [22,23]. Figure 2 shows the graph representing the per hour demand for transport at the MTA New York City subway.…”
Section: Global Impact Of Covid-19 Outbreak On Transport Systemsmentioning
confidence: 99%
“…Regression analysis revealed minimum demand for public transport was observed during COVID-19 in communities with higher proportions of critical employees and vulnerable groups (African American, Hispanic, Female, and people over 45 years of age). Around half of the agencies suffered a decline before the local spread of COVID-19 possibly began; most of these are in the Midwest of the United States [22,23]. Figure 2 shows the graph representing the per hour demand for transport at the MTA New York City subway.…”
Section: Global Impact Of Covid-19 Outbreak On Transport Systemsmentioning
confidence: 99%
“…Transit agencies and government leaders are faced with a social equity issue involving the continuation of service provision in communities that are transit dependent. In fact, by analyzing the transit demand data derived from a widely used transit navigation app in the U.S., Liu et al (2020) found that the disparate declines in transit demand reveal different degrees of dependence across communities. One significant result of their analysis is that the demand for transit during this pandemic is very low for people who can easily work at home and it is almost intact for people whose occupation requires a physical presence at the job’s location ( Liu et al 2020 ).…”
Section: Challenges and Policy Implicationsmentioning
confidence: 99%
“…In fact, by analyzing the transit demand data derived from a widely used transit navigation app in the U.S., Liu et al (2020) found that the disparate declines in transit demand reveal different degrees of dependence across communities. One significant result of their analysis is that the demand for transit during this pandemic is very low for people who can easily work at home and it is almost intact for people whose occupation requires a physical presence at the job’s location ( Liu et al 2020 ). While there is a need to modify the service given the decline in demand, transit providers must carefully weigh their decision to adjust (or reduce) service compared with the need to continue serving transit dependent communities.…”
Section: Challenges and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core procedure of them is to maintain the appropriate physical distances between people and to depend on the existence outdoors instead of indoors to avoid infection as possible [12]. According to LiuID, et al, [13], due to its collective attitude, its lower fare, and its importance for the broad classes of people, public transit is a vital mode of transportation on which many governments depend on to provide transportation systems. With returning to life after lockdown, many people are deeply anxious about being in crowded places such as train, metro and bus stations for fear of infection [14].…”
mentioning
confidence: 99%